Implementation of Teacher Certification Policies at SMK Negeri 1 Bitung - Taengetan, Meryati; Masengi, Evi E.; Tumbel, Goinpeace (Technium Social Sciences Journal, 2023)
Education in Indonesia has not been as expected, because educational institutions have not been able to produce quality Human Resources (HR). Even national education is considered to have failed to build national character. This is evident from the low value of the results of education quality report cards. This study aims to explain 1) How is the performance of certified teachers in carrying out the learning process at SMK Negeri 1 Bitung? 2) What factors hinder the low performance of certified teachers at SMK Negeri 1 Bitung? 3) How are the efforts made by the principal to overcome the obstacles to the performance of certified teachers. The method used in this research is a qualitative research method. The research was conducted at SMK Negeri 1 Bitung. Data collection techniques are observation, interviews and documentation studies. The data analysis technique used is data reduction, compiling in units, and interpreting and drawing conclusions. the results of the study are 1) The performance of certified teachers is still low both in discipline, namely being late, going home early, being lazy to go to class and in teaching skills and making learning tools; 2) Factors that inhibit the low performance of certified teachers, namely: Low ability (knowledge) and skills, Lack of motivation from superiors, Lack of control or supervision by the principal of various teacher activities in school, Lack of courage of the principal in taking strict action against teachers who break the rules, lack of training in making learning tools and do not master information technology; 3) Efforts made by the principal towards the expected performance of certified teachers are firm in reprimanding and giving sanctions to certified teachers who are lazy to teach if they do not heed if necessary their status as a teaching profession is removed, hold training in making learning tools and must master information technology and carry out continuous evaluations.